Transcutaneous Electrical Neurostimulation at the Second Stage of Medical Rehabilitation in Ischemic Stroke: a Controlled Randomized Study - Alexander B. Berger; Tatiana V. Konchugova (Вестник восстановительной медицины)
INTRODUCTION. Patients who have suffered a stroke require long-term and intensive rehabilitation measures to restore both vital and motor, cognitive, psycho-emotional and other functions of the body. Along with the use of physiotherapy methods, transcutaneous electrical neurostimulation can be used already at the stage of the patient’s stay in the intensive care unit; however, due to the lack of modern information on its effectiveness, this method is extremely rarely included in rehabilitation programs at the early stages.